The implementation of Iban vocabulary module in I-MMAPS (Interactive Multimedia-Based Mobile Application) for learning Iban language - Chachil, Ketty (Research Management Institute, Sarawak, 2017)
Mobile learning is the next generation of e-learning which utilizes the usage of mobile devices and wireless communication technology in education. Mobile learning is characterized by its potential for learning to be spontaneous, informal, personalized and ubiquitous. The traditional language learning context is experiencing radical changes and challenges as nowadays, language learners are demanding for better and improved access and convenience at lower costs and with the direct application of contents to their environment and needs. Currently, there is no locally produced mobile application to introduce the Iban language to adult learners. Therefore, this project proposes to enhance the interactive mobile application for learning Iban Language, by creating another module which is the vocabulary module. This mobile application will also serve as a repository for Iban Language that can be used to promote and preserve Iban Language among younger generations. The application consists of two modules, vocabulary and conversations, which incorporate pronunciations and spellings. This application is designed by adapting constructivism learning theory to provide the learners, a different approach in learning Iban Language based on their environments and situations. The outcome of this research is an enhanced interactive mobile application which includes Iban vocabulary module to attract users to learn the language. The analysis on users' acceptance toward the usage of the application in learning Iban Language, is done by adapting the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al.,2003). Based on the findings, respondents accepted the use of mobile devices and mobile application as a tool to help them to learn Iban Language. They were keen about the prospect of engaging in language learning using the mobile application in any time or place. In addition, they also perceived that the mobile application is easy to use and mobile learning is enjoyable.